MILLENNIAL GENERATION DECISIONS ARE BASED ON SOCIAL FACTORS AND PRICES WHICH ARE MODERATED BY LIFESTYLE - Hapsari, Ayu; Lisdayanti, Annisa (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
In the last few years, the fitness center industry has experienced significant growth, much of it due to the increasing interest of millennials in adopting healthy and active lifestyles. The current study explores the factors that influence millennials' decision to become members of the ruling class, with a particular emphasis on social and price factors. In addition to that, she describes how the principles of a good life might moderate the interaction between these factors and the process of developing a thesis. Since each variable X in this study significantly affects variable Y through variable Z as a moderating, findings are obtained using quantitative methods and statistical tools. The results show that, in addition to consideration of price, social factors significantly impact the millennial generation's decision to join a fitness center. Additionally, lifestyle selections have been demonstrated to lessen this effect, with specific lifestyle preferences either enhancing or minimizing the influence of social and financial variables on membership decisions. This study advances our knowledge of the factors that influence millennials' use of exercise facilities and provides insightful information to stakeholders and marketers in the fitness sector. A fitness center can more successfully target millennial groups by customizing its offers and marketing methods by understanding the connections between social variables, pricing policies, and individual lifestyle choices.